Teknologi Sistem Informasi Akuntansi dalam Minat Penggunaan Layanan Pembayaran Digital - Indah Triwijaya; Elen Puspitasari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Technological advancements have advanced quickly. Today's civilization successfully and efficiently mixes technologies with commerce. Everyone will find it simpler to do online transactions anytime, anywhere by using digital payment systems. The Accounting Information System have role to encourage utilizing digital payment. The aims of this study is to identify the variables that affect people's interest in utilizing digital payment systems with technology of accounting information system as a framework. There are 220 responses were recruited for this research. Regression analysis for hypotheses testing. According to the study's findings, interest in utilizing digital payment systems is significantly influenced by perceived usefulness, perceived ease of use, perceived trust, and perceived security.